The Mystical Interpetation Of Divine Love (Mahabbah) From The Perspective Al-Sulami’s Haqaiq Al-Tafsir - Sa’adah, Rifa Tsamrotus (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2020)
This study discusses the Quranic analysis of the word Maḥabbaḥ in al- Quran. This needs to be studied and requires some research because it has a general meaning, so it is worth analyzing. They know and understand Maḥabbaḥ in a limited way and for human needs only. Using a descriptive analytic method and Abū ‘Abd al-Rahmān al-Sulami's perspective on his own book, Haqāiq al-Tafsīr, this research answers how al-Sulami interprets the meaning of the Maḥabbaḥ in the Quran. This research finds that the Quran expresses the Maḥabbaḥ globally both to God and to humans. Some indications of the Quran suggest that the Maḥabbaḥ can arise because it begins with compassion and seeks to reach that love. This shows that Islam is concerned about the importance of love by providing several levels that must be achieved in order to be able to achieve it. This research focuses on the verses of Mahabbah from Surah Thāhā (20):39 which explain about the story of prophet Musa whom getting the specially Maḥabbaḥ. Thus, Surah Ᾱli-‘Imrān (3):31 explained about a way being a God’s lover and creating Maḥabbaḥ greatly.